Effects of Slaughter Age of Holstein Friesian Bulls on Meat Quality: Chemical Composition, Textural Characteristics, Sensory Attributes and Fatty Acid Profile - Diler, Abdulkerim; Yanar, Mete; Özdemir, Veysel Fatih; Aydin, Recep; Kaynar, Özgür; Palangi, Valiollah; Lackner, Maximilian; Koçyigit, Rıdvan (MDPI AG, 2022)
This study aimed to investigate the effects of slaughter age (young vs. old), muscle type (Longissimus dorsi (LD), Gluteus medius (GM)) and fat deposits (kidney knob and channel fat, subcutaneous fat, intramuscular fat) on chemical, organoleptic, textural characteristics and fatty acid composition of Holstein Friesian bull meat. For this purpose, the carcasses of 26 Holstein Friesian bulls that had been fattened on the same private farm were assigned to two experimental groups based on their age at slaughter: a young group (YG) (average age: 17.0 ± 1.0 months old) and an old group (OG) (average age: 22.0 ± 1.0 months old). The percentage of crude protein, panel tenderness score, polyunsaturated fatty acid (PUFA) and saturated fatty acid (SFA) content, the PUFA/SFA ratio and the hypocholesterolemic fatty acid (DFA)/hypercholesterolemic fatty acid (OFA) ratio of the bull carcasses decreased significantly with increasing slaughter age. By contrast, the OFA content of the carcasses significantly increased (p < 0.05) with increasing slaughter age. Advanced slaughter age resulted in lower panel tenderness scores. Additionally, the meat of the bulls in the OG was considered to be less healthy because of the less desirable fatty acid composition and nutritional indices, such as the PUFA/SFA and hypocholesterolemic/hypercholesterolemic ratios, compared to the meat from the bulls in the YG. Furthermore, the intramuscular fat and internal fat contained high percentages of PUFA and SFA and high PUFA/SFA and hypocholesterolemic/hypercholesterolemic ratios. Interestingly, the percentage of OFA content in the internal and intramuscular fat tissues decreased with increasing slaughter age. In conclusion, this study provided evidence that slaughter age and muscle and fat type are essential sources of variations in the textural characteristics, sensory panel attributes and fatty acid profile of meat from Holstein Friesian bulls.
Keywords: fatty acid profile; slaughter age; sensory evaluation; Chemical technology; TP1-1185; slaughter age; texture profile analysis; sensory evaluation; fatty acid profile; Article; texture profile analysis; 2. Zero hunger